Transformation of Emotional Violence in the Context of Online Communication in Social Networks. - Boiarshynova, Kateryna (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2021)
The article provides a theoretical overview of the main scientific approaches to the concept of "emotional violence", a comparison with similar concepts. Peculiarities of forms and manifestations of emotional violence in social networks are analyzed. The concept of cyberbullying and its modern types are considered.It has been established that difficulties in diagnosing and providing psychological assistance in emotional violence are associated with a distorted perception of modern formalized norms of social relations, which perceive and define threats, humiliation and insults as the norm of communication.To increase the effectiveness of combating cyberbullying requires a comprehensive solution: the inevitability of punishment for the crime, the definition of criteria for assessing the presence of signs of crime, which requires the formation of tools for assessing the consequences of harm. Therefore, there is an urgent need to identify and describe the definition of "psychological violence", to determine the psychological signs of emotional violence, to create tools to assess the harm done to the victim.An influential factor in combating cyberbullying is a collaborative approach: involving a wide range of professionals in the design and implementation of cyberbullying prevention programs, cyberbullying victim support programs, and zero tolerance programs for bullying, educating children and youth on media security and media literacy.
Keywords: emotional violence; cyberbullying; psychological violence; social networks